2020
DOI: 10.1016/j.biocon.2019.108398
|View full text |Cite
|
Sign up to set email alerts
|

Modelling cetacean morbillivirus outbreaks in an endangered killer whale population

Abstract: We would like to thank all of the many volunteers and staff that have contributed to the field work for Orca Survey that provided the photographs used in this study, as well the photographic ID catalogue for this population. We'd also like to thank Emma Foster for her work developing the network construction protocol used here. Role of funding source Data collection for this research was supported by funding from Earthwatch Institute and NOAA Fisheries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 65 publications
2
10
0
Order By: Relevance
“…Despite testing of postmortem serum, screening tissues by molecular studies and looking for cytoplasmic inclusions and syncytia microscopically, morbilliviruses, such as cetacean morbillivirus and morbillivirus antibodies have not been detected. This further supports the potential that exposure to these viruses could increase extinction risk in immunologically naïve and endangered killer whale populations like the southern residents [10,52].…”
Section: Infectious Diseasesupporting
confidence: 65%
“…Despite testing of postmortem serum, screening tissues by molecular studies and looking for cytoplasmic inclusions and syncytia microscopically, morbilliviruses, such as cetacean morbillivirus and morbillivirus antibodies have not been detected. This further supports the potential that exposure to these viruses could increase extinction risk in immunologically naïve and endangered killer whale populations like the southern residents [10,52].…”
Section: Infectious Diseasesupporting
confidence: 65%
“…This is especially concerning as many of Hawaii’s cetacean stocks are small, island-associated, resident populations that may be particularly vulnerable to any reduction in population size because of an already low number of breeding individuals such as the endangered main Hawaiian Islands insular false killer whale (Pseudorca crassidens) , estimated at only 167 individuals 38 . Novel disease is considered a major hurdle to endangered population recovery and even poses the threat of extinction as demonstrated in a recent effort to model the impact of a morbillivirus outbreak on endangered Southern resident killer whales ( Orcinus orca ) from the Pacific Northwest 39 . Southern resident killer whales were determined to be highly vulnerable to a disease outbreak 39 ; similarly, a novel disease outbreak among Hawaii’s endangered false killer whale population could have a disastrous impact.…”
Section: Discussionmentioning
confidence: 99%
“…Novel disease is considered a major hurdle to endangered population recovery and even poses the threat of extinction as demonstrated in a recent effort to model the impact of a morbillivirus outbreak on endangered Southern resident killer whales ( Orcinus orca ) from the Pacific Northwest 39 . Southern resident killer whales were determined to be highly vulnerable to a disease outbreak 39 ; similarly, a novel disease outbreak among Hawaii’s endangered false killer whale population could have a disastrous impact. Melon-headed whales ( Peponocephala electra ) in Hawaii are also genetically and behaviorally distinct, with a Kohala resident population of approximately 500 individuals inhabiting shallower waters off the Big Island 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, social networks could help managers understand disease risk and target vaccinations. While our systematic review found only three studies explicitly linking social networks and disease, more recent work has expanded the application of social networks to disease management, by estimating age and sex specific risk (Leu et al, 2020), explicitly modelling the spread of specific pathogens along with possible vaccination strategies (Weiss et al, 2020), and using randomisation procedures to determine the relevance of association networks to observed disease outbreaks (Powell et al, 2020). Further work determining the impact of social network structure on population-level disease risk in a comparative context could further inform conservation efforts.…”
Section: Future Research Directionsmentioning
confidence: 99%